Pengaruh Tata Kelola Perusahaan dan Volatilitas Arus Kas terhadap Persistensi Laba: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Yuni Maya Sari; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2021)
The study aims to test empirically the effect of corporate governance: independent board of commissioners, audit committee, managerial ownership and cash flow volatility on earnings persistence. This study uses a quantitative approach with a causal associative research type. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. By using purposive sampling method, 83 samples were selected. Earnings persistence is measured using measurements in research by Lipe (1990) and Sloan (1996). Independent board of commissioners, audit committee and managerial ownership are measured using measurements in research by Khafid (2012). And cash flow volatility is measured using measurements in research by Fanani (2010). The result show that the independent board of commissioners, audit committee and managerial ownership have no significant effect on earnings persistence and cash flow volatility has no significant effect on earning persistence. For further research, it is hped that this object can be reproduced and the research year because in this study it only examines manufacturing companies for the 2015-2019 observation year. In addition, further research can look for othe independent variabels if later doing the same research. The reaserch conducted is expexted to add independent variabels so that the results will be better.